Mạng nơ ron truyền thẳng cho điều khiển thích nghi các hệ thống phi tuyến - Hỷ, Chu Văn (Journal of Computer Science and Cybernetics, 2016)
Multilayer feedforward artificial neural networks are used in nonlinear adaptive control problems. In case of a feedback-linearizable plant, two networks are needed to model the unknown system and generate the feedback control. In general case, an inverse model adaptive control strategy is developed and analysed.